Disability and Virtual Worlds: New Frontiers of Appropriation - Boellstorff, Tom; Davis, Donna; Krueger, Alice (AoIR Selected Papers of Internet Research, 2013)
People with disabilities (PWD) remain highly marginalized worldwide; they continue to receive insufficient attention in internet research, where norms for design, implementation, and use often still presume an able-bodied self. Yet PWD have many insights to offer internet research with regard to new frontiers of appropriation. This panel brings together three scholars who engage in research, support, and advocacy with PWD in the virtual world Second Life. There is a tendency in internet studies to focus on new platforms, games, and devices, and to ignore or downplay the importance of those that have persisted for many years. Second Life, despite being ten years old, has hundreds of thousands of active users, including over 120 inworld support groups for PWD. It is larger than many of the small-scale communities that social scientists have studied for decades. Of course, Second Life is not indicative of all virtual worlds, and virtual worlds are not indicative of all online socialities. Nonetheless, the experiences, communities, and practices of PWDs in virtual worlds have much to teach us about the relationships between embodiment and the self, between human ability and technology, and between community, social change, and health. Disability is a social category into which almost all persons will fall at some point, given sufficient lifespan. The issues to which PWD respond through practices of appropriation in virtual worlds provide insight into emerging forms of resistance and appropriation online. Indeed, given that PWD are overrepresented in virtual worlds (with an estimated 20% of persons active in virtual worlds having a disability of some kind), we argue that theories of virtual-world identity, community, resistance, and appropriation will be more robust and meaningful when they take disability centrally into account. The three papers making up this panel are based on a set of researcher collaborations; we address both focused issues of disability and themes of broad significance. A central concern is how PWD in virtual worlds engage in modes of appropriation. In comparison to an earlier era where technologies were designed to aid PWD, we now see PWD directly involved in the appropriation of virtual contexts and infrastructures in ways that transform meaning and participation. These repurposings are shaped by factors including type of disability (chronic versus appearing later in life; more or less physically apparent; physical, mental, emotional, or sensory), goals (social support, leisure, education, rehabilitation), and genres of engagement (support groups, entertainment events, the construction of places). Yet through these differences we can identify a range of key themes of appropriation. Given that PWD have a higher likelihood of being unemployed or underemployed, these include questions of the political economy of social-technical practice. Questions of cooperation and organization are also central, including the fact that some PWD rely on caregivers who may also be involved in online activities with them, or in addition to their participation. The case studies examined in the papers include studies of persons with Parkinson’s disease who find value not just in avatar embodiment, but in the construction of buildings and landscapes. These PWD find virtual worlds important for social support, but also for unleashing creativity and even for the possibility of therapeutic effects linked to watching their avatars perform certain kinds of movements. Additionally, we discuss groups including people with a wider range of disabilities, examining issues including relationships to one’s avatar, self-efficacy, responding to isolation, and the possible dangers of addiction, frustration, and lack of confidentiality. We also step back from these fine-grained analysis to examine how the experiences of PWD in virtual worlds can provide conceptual tools for rethinking current debates regarding the “materiality of information” and the dualism between mind and body.